Performances Enhancement of a‐Si:H Thin Film Photovoltaic Cells by Incorporating Silver Nanoparticles. Issue 17 (26th March 2018) - Pokam Kuisseu, Pauline S.; Yu, Peiqing; Pingault, Timothée; Blondeau, Jean‐Philippe; Ntsoenzok, Esidor; Andreazza, Caroline; Roussel, Julien; Mustapha, Elyaakoubi; Meot, Jacques; Jaffré, Alexandre; Longeaud, Christophe
Abstract : a‐Si:H thin films‐based solar cells offer the benefit of reducing material consumption and fabrication costs. However, such thin absorbing layer reduces the photovoltaic efficiency, due to their poor light absorption at red and near‐infrared wavelengths. Metal NPs such as silver (Ag) can exhibit strong localized surface plasmon (LSP) resonances at different wavelength ranges, allowing increasing the light absorption in the active layer. The goal of this study is to perform an optimal structure of Ag NPs allowing to optimize the light absorption within the a‐Si:H solar cells by means of scattering. Ag layers are deposited on two different SnO2 substrates (with different roughness). After annealing, quasi‐spherical shaped of Ag NPs with diameters ranging from 10 to 130 nm are obtained. UV‐visible spectroscopy displays one LSP resonance around 560 nm with the less rough substrate, while three LSP resonances around 560, 700, and 850 nm are observed with roughest substrate. These differences are mainly due to the size distribution of NPs and underline the strong influence of the surface roughness and the coupling effect on the NPs behavior. a‐Si:H thin film solar cells with Ag NPs are subsequently elaborated. Spectral response shows an improvement of about 14–15%. Abstract : Silver nanoparticles (Ag NPs) are used to increase the light absorption within a‐Si:H solar cells. These nanoparticles are fabricated on two different SnO2 substrates, with different roughness. Depending on the surface roughness, different size distribution and localized surface plasmon resonances are obtained. Measurements of spectral response of a‐Si:H solar cells built with Ag NPs show an improvement of about 14–15%.